Increased expression of pentraxin 3 in placental tissues from patients with unexplained recurrent pregnancy loss - Zeybek S; Tepeli E; Cetin GO; Caner V; Senol H; Yildirim B; Bagci G (Balkan Journal of Medical Genetics, 2019)
Pentraxin 3 (PTX3), a prototypical member of the long pentraxin subfamily, is a evolutionarily conserved multimeric pattern recognition receptor involved in the humoral component of the innate immune system. Pentraxin 3 is released when tissue is stressed or damaged, and interacts with many different ligands. Pentraxin 3 exerts a pivotal role both as a regulator and as an indicator of inflammatory response in the pathogenesis of many diseases such as sepsis, vasculitis and preeclampsia. Uncontrolled inflammatory response is considered a major cause of unexplained recurrent pregnancy loss (URPL). We determined the PTX3 messenger ribonucleic acid (mRNA) and protein expression levels in placentai tissues from 50 women with URPL, and made comparison with those in 50 age-matched control subjects. In quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry analyses, PTX3 mRNA and protein levels, respectively, were significantly increased in URPL patients compared with their respective controls (p = 0.0001). Although no significant correlations were identified between PTX3 expression levels and clinical parameters such as maternal age, numbers of previous pregnancy losses, and gestational age at miscarriage, PTX3 mRNA expression was significantly higher in patients with no live births than in women with previous live births (p = 0.0001). Our study suggests that tissue-specific expression of PTX3 is associated with URPL. Further larger studies are required to determine whether PTX3 expression can be used as a biomarker to manage URPL in routine clinical practice.